Proximal Overresection During Femoral Osteochondroplasty Negatively Affects the Distractive Stability of the Hip Joint: A Cadaver Study. Issue 11 (September 2021) - Lazaro, Lionel E.; Lim, Daniel P.; Nelson, Trevor J.; Eberlein, Sam A.; Banffy, Michael B.; Metzger, Melodie F.
Background: Contact between the acetabular labrum and articular cartilage of the femoral head creates a suction seal that helps maintain stability of the femoral head in the acetabulum. A femoral osteochodroplasty may occasionally extend proximally into the femoral head, diminishing the articular surface area available for sealing contact. Purpose: To determine whether proximal overresection decreases the rotational and distractive stability of the hip joint. Study Design: Controlled laboratory study. Methods: Six hemipelvises in the following conditions were tested: intact, T-capsulotomy, osteochondroplasty to the physeal scar, and 5- and 10-mm proximal extension. The pelvis was secured to a metal plate, and the femur was potted and attached to a multiaxial hip jig. Specimens were axially distracted using a load from 0 to 150 N. For rotational stability testing, 5 N·m of internal and external torque was applied. Both tests were performed at different angles of flexion (0°, 15°, 30°, 60°, 90°). Displacement and rotation were recorded using a 3-dimensional motion tracking system. Results: The T-capsulotomy decreased the distractive stability of the hip joint. A femoral osteochondroplasty up to the physeal scar did not seem to affect the distractive stability. However, a proximal extension of the resection by 5 and 10 mm increased axial instability at every angle of flexion tested, with the greatest increase observed at larger angles of flexion ( P < .01). External rotation increased significantly after T-capsulotomy in smaller angles of flexion (0°, P = .01; 15°, P = .01; 30°, P = .03). Femoral osteochondroplasty did not create further external rotational instability, except when the resection was extended 10 mm proximally and the hip was in 90° of flexion ( P = .04). Conclusion: This cadaveric study demonstrated that proximal extension of osteochondroplasty into the femoral head compromises the distractive stability of the hip joint but does not affect hip rotational stability. Clinical Relevance: Clinically, this study highlights the importance of accuracy when performing femoral osteochondroplasty to minimize proximal extension that may increase iatrogenic instability of the hip joint.